Riba According to The Al-Quran View: Thematic Tafsir Study About Riba Verses - Muhammad Halaby (International Journal of Islamic Thought and Humanities, 2022)
Riba is discussed by the Qur'an through four stages, similar to the steps of khamr prohibition (hard drink). The first stage of merely describing the negative element, namely surah Ar-Rum verse 39. Then followed the cues of its haram (Surah an-Nisa ': 161). Later in the third stage, as expressly stated prohibition of one form, is doubled (Surah al-Imran: 130). Finally, total prohibition and in its various forms is the QS. al-Baqarah 275-279. Islam prohibits the practice of usury, for several reasons, among others: first, Allah and His Messenger forbid or make it haram. Second, because of usury requires taking someone else's property with no compensation (vanity). Third, by usury, people become lazy attempt lawful shara '. Fourth, when usury is ingrained in a person, then that person prefers to raise money because the money will benefit cattle greater than the trade and done with no difficulty. Fifth, usury causes ruptures benevolence toward our fellow human beings by way of debt or eliminate the usefulness of debt, then it is more likely to extort usury of the poor rather than helping the poor.